Development Of Pesantren In The Era Of Globalization (Case Study of Riyadlusorfi Wal Mantiq's Pesantren Strategy in Developing Pesantren in the Era of Globalization of Education) - Irpan Ilmi; Juliani Juliani; Mohamad Erihadiana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This research aims to analyze the strategies used by the Riyadlushorfi Wal Mantiq Islamic Boarding School in developing Islamic boarding schools in the era of globalization of education. The research method used is a qualitative method with a case study approach. Data was obtained through participant observation, in-depth interviews, and analysis of related documents. The research results show that the Riyadlushorfi Wal Mantiq Islamic Boarding School implements several important strategies to develop Islamic boarding schools in the era of globalization of education. First, this Islamic boarding school adopts a holistic educational approach, which includes religious, academic and character aspects. Islamic boarding schools ensure that students not only gain a strong understanding of religion, but also academic skills that are relevant to the demands of the times. Second, the Riyadlushorfi Wal Mantiq Islamic Boarding School applies information and communication technology in the educational process. Islamic boarding schools use technology to improve administrative efficiency and internal communication. Third, this Islamic boarding school establishes partnerships with other educational institutions, including universities and research institutions. Through this collaboration, Islamic boarding schools gain access to additional resources, training for students and ustadz, and collaboration opportunities on educational projects. Fourth. Islamic boarding schools prepare students to become leaders who are able to adapt and contribute to an increasingly global society. This research provides insight into the strategies used by the Riyadlushorfi Wal Mantiq Islamic Boarding School in developing Islamic boarding schools in the era of globalization of education. The results of this research can be a reference for other Islamic boarding schools in developing relevant strategies to face the challenges and opportunities posed by the globalization of education.